Neonatal Thyroid-Stimulating Hormone Reference Intervals in Multi-Ethnics Population - Hery Priyanto; Fauqa Arinil Aulia; Hartono Kahar; Muhammad Faizi; Ferdy Royland Marpaung; Aryati Aryati (Children)
(1) Background: This study is designed to establish thyroid-stimulating hormone (TSH) reference intervals tailored to different neonatal age groups and Indonesian local populations. (2) Methods: Dried blood spot neonatal TSH values, from 1 January 2022 to 31 December 2023, were used to establish the neonatal TSH reference intervals partitioned by sex, gestational age, and ethnic group at different neonatal ages. (3) Results: A significant difference in the reference intervals value was observed in sex, gestational ages, and parental ethnicity groups in different neonatal age subgroups (p < 0.05). Male reference intervals were significantly higher than those of females at all neonatal ages. Late and post-term gestational age categories reference intervals were higher than early and full-term. Among the ethnic groups, Madurese had a higher upper limit TSH reference interval. (4) Conclusions: Our neonatal TSH reference intervals were needed to provide a reference adapted to the local population of Indonesia.